2018
DOI: 10.3386/w24864
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Industry Interactions: Persuasion and Welfare

Abstract: In markets where consumers seek expert advice regarding purchases, firms seek to influence experts, raising concerns about biased advice. Assessing firm-expert interactions requires identifying their causal impact on demand, amidst frictions like market power. We study pharmaceutical firms' payments to physicians, leveraging instrumental variables based on regional spillovers from hospitals' conflict-of-interest policies and market shocks due to patent expiration. We find that the average payment increases pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“… 11. The magnitude of variation is larger than, but similar to, that documented for medical supplies in recent research, which found coefficients of variation ranging from 9% to 35% (Grennan & Swanson, 2018). …”
supporting
confidence: 76%
See 2 more Smart Citations
“… 11. The magnitude of variation is larger than, but similar to, that documented for medical supplies in recent research, which found coefficients of variation ranging from 9% to 35% (Grennan & Swanson, 2018). …”
supporting
confidence: 76%
“…Our results contribute to the growing literature in health economics on price dispersion for medical supplies (Grennan, 2013;Grennan & Swanson, 2018), pharmaceuticals (Kyle, Allsbrook, & Shulman, 2008), and medical services (Cooper et al, 2019;Dunn, Liebman, & Shapiro, 2017;Newman, Parente, Barrette, & Kennedy, 2016;Xu et al, 2015). 2 The previous studies looking at medical services have relied on data sets that do not include explicit information on the payer with which each patient is associated.…”
Section: New Contributionmentioning
confidence: 72%
See 1 more Smart Citation
“…The PPSA was established to provide transparency regarding pharmaceutical payments to physicians and to deter payments and promote ethical conduct. Previous research (e.g., [4,5,15,16,19,22]) on the PPSA's impact has approached the question from several angles and presented very diverse findings due to the complexity of the issue. To understand the PPSA's impact, researchers must consider multiple stakeholders, various fields of medicine, and the dynamics among physicians, pharmaceutical companies, hospitals, patients, and policy makers.…”
Section: Introductionmentioning
confidence: 99%
“…5,13 Other studies have found that region-specific industry payments for specific brand-name drugs and devices are associated with increased brand-name drug and device use. 14-16…”
mentioning
confidence: 99%